Dispersion of irregular particles during free fall - A.F.M., Fadzir; Siti Ilyani, Rani; Jolius, Gimbun (IOP Publishing, 2020)
This paper describes an experimental set up to examine the relationship between powder properties on powder flow pattern during filling operation. For this purpose, the free fall velocities of four types of agricultural dusts (i.e. castor sugar, oat, semolina and tea powder) in a rectangular enclosure were captured using a Particle Image Velocimetry (PIV). The result reveals that oat powder portrayed greater cloud dispersion due to its flaky shape and a lower bulk density. The characteristics of oat powder allowed more air to be dragged into the particle stream and forced the particle to be dispersed and suspended in air due to drag force and terminal velocity. The result presented here may facilitate improvements in dust control and measures in powder industries.